2005
DOI: 10.1097/01.mop.0000158729.18551.dd
|View full text |Cite
|
Sign up to set email alerts
|

Update on Munchausen syndrome by proxy

Abstract: In spite of these challenges, the high mortality and recidivism rates associated with MBP make it imperative that pediatricians be familiar with the condition, the subtle signs and symptoms with which it may present, and methods to best protect the children in their care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0
9

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 56 publications
(49 citation statements)
references
References 19 publications
0
40
0
9
Order By: Relevance
“…4,36 MSbP abusers are usually very knowledgeable about medical treatment options through experience as a patient, through training as a child care provider or health care provider, or through library and Internet research. 12 Hall et al 37 reported that in 85% of their 41 video-documented cases of MSbP, one or both parents had training in a field related to health care or in day care.…”
Section: Perpetrators: It's All About Me!mentioning
confidence: 99%
See 4 more Smart Citations
“…4,36 MSbP abusers are usually very knowledgeable about medical treatment options through experience as a patient, through training as a child care provider or health care provider, or through library and Internet research. 12 Hall et al 37 reported that in 85% of their 41 video-documented cases of MSbP, one or both parents had training in a field related to health care or in day care.…”
Section: Perpetrators: It's All About Me!mentioning
confidence: 99%
“…However, covert www.ccnonline.org videotapes have repeatedly recorded that these same parents generally ignore or even mistreat the child when convinced no one is there to observe their performance (Table 3). 12,31,37 …”
Section: Perpetrators: It's All About Me!mentioning
confidence: 99%
See 3 more Smart Citations